Entecavir or tenofovir monotherapy prevents HBV recurrence in liver transplant recipients: A 5-year follow-up study after hepatitis B immunoglobulin withdrawal. Issue 9 (September 2018) - Manini, Matteo A.; Whitehouse, Gavin; Bruce, Matthew; Passerini, Matteo; Lim, Tiong Y.; Carey, Ivana; Considine, Aisling; Lampertico, Pietro; Suddle, Abid; Heaton, Nigel; Heneghan, Michael; Agarwal, Kosh
Abstract: Background: Recent data suggest that oral third-generation nucleos(t)ide analogs (NA) monoprophylaxis following hepatitis B immunoglobulin (HBIg) withdrawal may be effective to prevent HBV reinfection after liver transplantation (LT). Patients and methods: Between 01/2010 and 03/2012, all HBV monoinfected and HBV/HDV co-infected LT patients followed in our centre withdrew HBIg ± NA and were commenced on either ETV or TDF as monotherapy. Results: Seventy-seven patients were included in the study (55% TDF, 45% ETV). Group A comprised 69 HBV monoinfected patients and Group B 8 HBV/HDV co-infected patients. After HBIg withdrawal, Groups A and B patients were followed for 69 (range 13–83) months and 61 (range 31–78) months, respectively. No Group B patients had HBsAg or HBV DNA recurrence, while 6 (9%) Group A patients became HBsAg-positive after a median of 18 (range 1–40) months. The cumulative 5-year incidence of HBsAg recurrence was 9%. All 6 patients demonstrated undetectable HBV-DNA levels and stable graft function during 30 months of additional follow-up. In 3/6 patients, seroconversion was transitory, while the remaining 3 showed HBsAg levels <0.13 IU/mL over the entire period of observation. Pre-LT HCC emerged as the strongest predictor of HBsAg recurrence. Conclusion: HBIG can be safely discontinued in HBsAgpositive LT recipients and replaced by ETV or TDF monotherapy.